2007
DOI: 10.1186/1472-6963-7-98
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of literacy and heart failure in adults with diabetes

Abstract: Background: Although reading ability may impact educational strategies and management of heart failure (HF), the prevalence of limited literacy in patients with HF is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 28 publications
(35 reference statements)
3
38
1
Order By: Relevance
“…But this rate was much lower than the 52% found in high school students in Texas US (Ghaddar et al, 2012), and 58% (Cheryl et al, 2011), 72% (Morrow et al, 2006) and 73% (Laramee et al, 2007) in three samples of ambulatory heart failure patients. A recent study conducted in Taiwan found that nearly 41% of adolescents could be classified as high health literacy, 49% moderate, and nearly 10% low (Chang, 2010), and this prevalence was much higher than that found in our study.…”
Section: Discussionmentioning
confidence: 70%
“…But this rate was much lower than the 52% found in high school students in Texas US (Ghaddar et al, 2012), and 58% (Cheryl et al, 2011), 72% (Morrow et al, 2006) and 73% (Laramee et al, 2007) in three samples of ambulatory heart failure patients. A recent study conducted in Taiwan found that nearly 41% of adolescents could be classified as high health literacy, 49% moderate, and nearly 10% low (Chang, 2010), and this prevalence was much higher than that found in our study.…”
Section: Discussionmentioning
confidence: 70%
“…A significant body of research has consistently documented a strong, graded relationship between both education and literacy skills with health knowledge [10][11][12]. Fewer studies to date have evaluated the relationship between literacy and health outcomes, including mortality; those documenting positive associations found literacy to be the more dominant predictor compared to years of education [6][7][8].…”
Section: Introductionmentioning
confidence: 96%
“…Recent investigations have examined the role of adult literacy skills as a mediating factor to the education-health relationship [6][7][8]. Literacy is a multifaceted concept that includes many of the cognitive and social skills learned through formal education processes; reading and numeracy are just a few of the fundamental components [9].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have revealed that limited HL is related to worse physical and mental health and poor healthcare utilization (Williams et al, 1998a;Gazmararian et al, 1999;Kalichman et al, 2000;Baker et al, 2002;Schillinger et al, 2002;Scott et al, 2002;Wolf et al, 2004;Howard et al, 2005;Wolf et al, 2005;Davis et al, 2006;Sudore et al, 2006;Baker et al, 2007;Laramee et al, 2007;Bennett et al, 2009;Tokuda et al, 2009;Berkman et al, 2011b). However, those studies focussed mainly on functional HL (Williams et al, 1998a,b;Kalichman et al, 2000;Schillinger et al, 2002;Laramee et al, 2007;Guerra et al, 2008;Chaudhry et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, those studies focussed mainly on functional HL (Williams et al, 1998a,b;Kalichman et al, 2000;Schillinger et al, 2002;Laramee et al, 2007;Guerra et al, 2008;Chaudhry et al, 2011). Despite recent calls for measuring HL in a community setting (Nutbeam, 2008;Pleasant and Kuruvilla, 2008;Peerson and Saunders, 2009), studies have been limited to measuring HL and health in a community (Wolf et al, 2005;Wolf et al, 2007;Bennett et al, 2009;Wolf et al, 2010).…”
Section: Introductionmentioning
confidence: 99%